COMPARATIVE EVALUATION OF P53 IN NORMAL BREAST, FIBROADENOMA, AND CARCINOMA BREAST - KT ATHULYA KRISHNA KUMAR; ABHILASH NP; VANISRI HR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to analyze as well as compare the immunohistochemical expression of P53 in normal breast tissue and cases of fibroadenoma and carcinoma breast. Methods: The present study was a retrospective analysis over a period of 1 year (2022–2023). A total of 60 cases comprising 10 cases of normal breast tissue, 20 cases of fibroadenoma breast, and 30 cases of carcinoma breast were included. Immunohistochemical staining by P53 antigen was performed and slides were graded accordingly as Grade 0, 1, and 2 depending on the staining intensity and percentage. Results: Correlation of P53 staining across the spectrum of normal breast, fibroadenoma, and carcinoma breast showed a significant association (p=0.01). There was no significant association between the age and level of P53 expression (p=0.1). On evaluating the association between other clinicopathological variables and grade of P53 expression, we found a significant association with regards to tumor size (p=0.0006), tumor grade (p=0.043), lymph-vascular invasion (p=0.019), and nodal metastasis (p=0.025). Conclusion: P53 may be a possible prognostic marker, to help in better therapeutic management of cases of breast carcinoma.